Research of mechanical treatment of stormwater runoffs formed on objects of automobile and road complex - Юрченко, Валентина Александровна; Мельникова, Оксана Григорьевна; Бахарева, Анна рьевна; Ячник, Мария Владимировна (Eastern-European Journal of Enterprise Technologies, 2015)
Experimental research revealed that the concentration of oil products in surface wastewater, formed in winter and summer on the objects of automobile and road complex - gas stations, car parks and roads, greatly exceeds the MPC for discharge into water bodies. In stormwater runoffs at gas stations and car parks, the concentration of oil products has higher values than in surface wastewater, formed on the roads, despite the low traffic level. In surface wastewater, formed at gas stations and car parks, conditionally heavy fractions of oil products, more efficiently removable during settling prevail. The effect of surface wastewater treatment from oil products (maximum 80 %) depends on several parameters, the most significant of which is the concentration of suspended solids.